The Prevalence and Associated Distress of Physical and Psychological Symptoms in Patients With Advanced Heart Failure Attending a South African Medical Center. Issue 4 (July 2016) - Lokker, Martine E.; Gwyther, Liz; Riley, Jillian P.; van Zuylen, Lia; van der Heide, Agnes; Harding, Richard
Abstract : Background: Despite the high prevalence of heart failure in low- and middle-income countries, evidence concerning patient-reported burden of disease in advanced heart failure is lacking. Objective: The aim of this study is to measure patient-reported symptom prevalence and correlates of symptom burden in patients with advanced heart failure. Methods: Adult patients diagnosed with New York heart Association (NYHA) stage III or IV heart failure were recruited from the emergency unit, emergency ward, cardiology ward, general medicine wards, and outpatient cardiology clinic of a public hospital in South Africa. Patients were interviewed by researchers using the Memorial Symptom Assessment Scale–Short Form, a well-validated multidimensional instrument that assesses presence and distress of 32 symptoms. Results: A total of 230 patients (response, 99.1%), 90% NYHA III and 10% NYHA IV (12% newly diagnosed), with a mean age of 58 years, were included. Forty-five percent were women, 14% had completed high school, and 26% reported having no income. Mean Karnofsky Performance Status Score was 50%. Patients reported a mean of 19 symptoms. Physical symptoms with a high prevalence were shortness of breath (95.2%), feeling drowsy/tired (93.0%), and pain (91.3%). Psychological symptoms with a high prevalence were worrying (94.3%), feeling irritable (93.5%), and feeling sad (93.0%). Multivariate linear regression analyses, with total number of symptoms as dependent variable, showed no association between number of symptoms and gender, education, number of healthcare contacts in the last 3 months, years since diagnosis, or comorbidities. Increased number of symptoms was significantly associated with higher age ( b = 0.054, P = .042), no income ( b = −2.457, P = .013), and fewer hospitalizations in the last 12 months ( b = −1.032, P = .017). Conclusions: Patients with advanced heart failure attending a medical center in South Africa experience high prevalence of symptoms and report high levels of burden associated with these symptoms. Improved compliance with national and global treatment recommendations could contribute to reduced symptom burden. Healthcare professionals should consider incorporating palliative care into the care for these patients.